Fasting and re-feeding effects for the new measurement to improve feed efficiency traits in Pacific abalone (Haliotis discus hannai) - Ziheng Yin; Wenchao Yu; Junyu Liu; Jianzhong Weng; Jie Huang; Miaoqin Huang; Jinwei Ke; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture Reports)
To speed up the process of measuring abalone for feed efficiency traits and apply the technique in commercial breeding programs, we developed a new evaluation index by fasting and re-feeding treatment. A total of 400 ten-month-old Pacific abalone (Haliotis discus hannai) were randomly sampled. To evaluate feed efficiency traits, each abalone was cultured for 72 days using the previously established single-individual system. After that, the FER was ranked after removing outliers, the top and bottom 150 individuals were exposed to different durations of fasting stress (3, 7, 10, 14, and 21 days), which was followed by single-individual re-feeding treatments. The fluctuations in body weight of each abalone during this process were recorded. The difference in the ability to cope with fasting stress and re-feed between the high- and low-FER (feed efficiency ratio) groups was analyzed. The findings demonstrated that the specific weight loss rate (SWLR) of the high- and low-FER groups of Pacific abalone differed after varying durations of fasting. The results of the correlation analysis between FER and weight change index showed that SWLR was negatively correlated with FER during stress, and the correlation of the 7-day fasting group (S7) was the highest (r = –0.71). The “rapid growth stage” during re-feeding was positively correlated with FER, and the correlation between the body weight gain (BWG) of days 14–28 and FER in the 10-day fasting group (S10) was the highest (r = 0.79). The results indicate that there is significant variation in the capacity of abalone to resist fasting stress and re-feeding, and this is associated with feed efficiency. The above measured indicators (SWLR of the S7 group and BWG14–28 of the S10 group) may be used as indirect indicators for feed efficiency traits, and these indicators have application value in abalone breeding.